[Assembling of parts at the sugar factory] - (:unkn) unknown (The Public Relations Department. Caroni (1975) Limited, Trinidad and Tobago, 2013)
Assembling the parts for the front loader at one of Caroni (1975) Limited's factories.
Cataloger's title
Keywords: Sugar factories -- Trinidad and Tobago; Agricultural machinery -- Parts - Trinidad and Tobago; Caroni (1975) Limited